2006
DOI: 10.1593/neo.06304
|View full text |Cite|
|
Sign up to set email alerts
|

Noninvasive Optical Tracking of Red Fluorescent Protein-Expressing Cancer Cells in a Model of Metastatic Breast Cancer

Abstract: We have evaluated the use of the Xenogen IVIS 200 imaging system for real-time fluorescence protein-based optical imaging of metastatic progression in live animals. We found that green fluorescent protein-expressing cells (100 x 10(6)) were not detectable in a mouse cadaver phantom experiment. However, a 10-fold lower number of tdTomato-expressing cells were easily detected. Mammary fat pad xenografts of stable MDA-MB-231-tdTomato cells were generated for the imaging of metastatic progression. At 2 weeks posti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 31 publications
1
76
0
Order By: Relevance
“…Several newer mutants of mrfp1 with increased photostability and brightness (mCherry and tdTomato) or far-red emission spectra (mPlum and mRaspberry at 649 and 625 nm) have been reported (29). Based on recent tests in xenograft models of metastatic breast cancer (30), tdTomato would be the most likely to provide a further improvement over mrfp1.…”
Section: Discussionmentioning
confidence: 99%
“…Several newer mutants of mrfp1 with increased photostability and brightness (mCherry and tdTomato) or far-red emission spectra (mPlum and mRaspberry at 649 and 625 nm) have been reported (29). Based on recent tests in xenograft models of metastatic breast cancer (30), tdTomato would be the most likely to provide a further improvement over mrfp1.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly pertinent for monitoring the behavior of static cell populations (e.g., tumor xenografts) (463), and for investigating the bio- distribution, underlying mechanisms, and functional benefits of cell-based therapies, thus expediting the clinical translation of these promising treatment strategies. Molecular imaging will likely play a key role in the clinical translation of cell-based therapies.…”
Section: E Cell Trackingmentioning
confidence: 99%
“…1 In addition, the MDA-MB-231 cells that stably express the bright red fluorescence protein used in that study were easily identified in post mortem tissue preparations. Thus, macroscopic to microscopic detection was achieved.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, fluorescence based optical imaging is limited to detection depths of, at best, several millimeters below the surface. 1 On the other hand MRI can not resolve microscopic structures in ex-vivo samples. This exemplifies that multi-modality detection systems are inherently more flexible and supply complementary data sets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation